Vallástanítás mint szent kötelesség - PÜSÖK, Sarolta (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2025)
Religious Education as a Sacred Duty. The following study deals with one of the most important tasks of the Christian community, namely conveying Christ’s message of joy to children, with particular reference to the situation of the Reformed Church in Romania. The first half of the study looks back on three and a half decades of religious education in schools since the change of regime, focusing in particular on the initial period, which was marked by a kind of crisis intervention, with the rapid reorganization of activities that had been banned during the communist era, despite the lack of even the most basic resources. The second subchapter discusses issues related to the development of infrastructure, teacher training, and the development of religious education curricula. The third subchapter primarily reflects on the major changes occurring at the societal level and how intergenerational differences and postmodern challenges affect education. The second half of the study analyses the closely related areas of religious education separately for the sake of clarity: family, congregation, and school. It attempts to outline the future directions of current experiences. In addition to social changes affecting families, the vulnerability of families must also be taken into account. Despite all this, the family remains the most important arena for religious education, which young parents need to be made aware of. Congregations have an ancient tradition of religious education for children, but recent worrying trends should not be ignored. Among these, the study highlights the phenomenon that many parents no longer require the children’s programmes offered by the congregation because they are satisfied with religious education in school. Following this diagnosis, the only viable path forward is to make these opportunities more attractive, not least through improvements in the marketing of spiritual values. The third area seeks answers to the question of what constitutes a good denominational school, while also reflecting on religious education in state schools. In Romania, everyone has the right to raise and educate their children according to their own traditions. Beyond the legal framework, the goal remains to ensure the quality of education, to promote acceptance of others and to encourage children to stand up for their own beliefs, in such a way that religious education is both child-friendly and Christ-centred.